Special educational needs of children and adolescents with diabetes diagnosis - García Cedillo, Ismael; Lozano Cabral, Karla (IE Revista de Investigación Educativa de la REDIECH, 2021)
Diabetes in pediatric ages can have serious physical consequences and, consequently, compromise the students’ academic trajectory. The purpose of the study was to identify if students with diabetes mellitus diagnosis present special educational needs. Nine children and adolescents with type 1 and 2 diabetes mellitus, between the ages of 10 and 17, who were receiving medical attention in a public hospital in the city of San Luis Potosí (Mexico) participated; alongside their parents, teachers, and a classmate of each student. Brief interviews to parents, teachers and schoolmates were done; the Wechsler Intelligence Scale for Children (WISC-IV) were applied to participants. Also, the Survey on Strategies for Strengthening Learning and the Guide for the Evaluation of Inclusive Practices in the Classroom were applied to teachers. The students’ grades were registered. It was found that only two students qualify to be considered to have special educational needs; their needs were not attended by their teachers.